Kant's Anthropology as a Theory of Integration - Lyssy, Ansgar (Studia Kantiana, 2023)
The Anthropology has been criticized for the heterogeneity of its content and its "merely" empirical direction. In this presentation, I want to offer a reading that turns these two features into advantages and also helps us clarify the type of knowledge that anthropology provides. Apart from being an applied science with its unique object, methods, and principles of inquiry, Kant's Anthropology also relates different other fields of knowledge and inquiry to each other, i.e., integrates them into a unified whole. Read together with a few ideas from Kant's broader anthropological project, the Anthropology can thus be said not only to develop an empirical theory of human nature, but also to provide a meta-theoretical framework concerning the relations between different theoretical ideas of human nature. Teleological judgments and prudential knowledge play a crucial role in this framework, as they allow us to relate different empirical observations and subfields of inquiry to the same purposes. In this regard, Kant's anthropological project bears striking structural similarities to the Darwinian theory of evolution.